# Simplifying Expressions

Not what you're looking for? Search our solutions OR ask your own Custom question.

3(x-2)-6x=15

Simplify as much as possible

-7(x+7)= -5x-9+5(-8x-6)=?

Â© BrainMass Inc. brainmass.com March 4, 2021, 7:59 pm ad1c9bdddfhttps://brainmass.com/math/basic-algebra/simplifying-expression-problems-136766

#### Solution Preview

Please see the attached file for the complete solution.

3(x-2)-6x=15

first using the distributive property of the multiplication

3x -3 *2 - 6x = ...

#### Solution Summary

An expression is simplified in the solution.

$2.49